ANALISIS KINERJA KEUANGAN DAERAH DAN INDEKS PEMBANGUNAN MANUSIA PROVINSI MALUKU UTARA - Taslim, Fadli Ali; Pratama, Rheza (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This study aims to determine the effect of the Regional Financial Independence Ratio, PAD Effectiveness Ratio and Efficiency Ratio on the Human Development Index (HDI). The population used in this study were 10 districts/cities of North Maluku province using purposive sampling method. The type of data collected is secondary data from the Central Statistics Agency (BPS) and the Regional Financial and Asset Management Agency (FAMA) of North Maluku Province. In this study using panel data regression analysis tool.The results of this study indicate that the Independence Ratio has a significant negative effect on the human development index, the PAD Effectiveness Ratio has a significant negative effect on the human development index and the Efficiency Ratio has a significant negative effect on the human development index